Mortality of workers compensated for silicosis during the period 1959-1963 in the Veneto region of Italy. - Zambon, Paola; Simonato, Lorenzo; Mastrangelo, G; Winkelmann, Regina; Saia, B; Crepet, M (Scandinavian Journal of Work, Environment & Health, 1987)
After reports appeared from other countries indicating an excess risk of lung cancer among silicotics, a cohort of workers compensated for silicosis during the period 1959-1963 in the Veneto region of Italy was constructed and followed for mortality through 1984. The results of the study showed a large mortality excess for infectious diseases (180 observed versus 9.5 expected), due to silicotuberculosis, and for diseases of the respiratory system (270 observed versus 33.5 expected) due to silicosis. An elevated standardized mortality ratio of 239 (70 observed versus 29.3 expected) from lung cancer was also detected. An increasing pattern was observed with time since first exposure, while the relationship with employment category and duration of exposure was less clear-cut. The lung cancer excess was also strongly associated with cigarette smoking, there being a dose-response relationship with daily cigarette consumption. The study confirms the results from other epidemiologic studies on silicotics which show this pathological condition to be associated with increased lung cancer mortality.